Heparins mediate the multimer assembly of secreted Noggin. (19th August 2022) - Heide, Fabian; Legare, Scott; To, Vu; Gupta, Monika; Gabir, Haben; Imhof, Thomas; Moya‐Torres, Aniel; McDougall, Matthew; Meier, Markus; Koch, Manuel; Stetefeld, Jörg
Abstract: Extracellular matrix proteins are most often defined by their direct function that involves receptor binding and subsequent downstream signaling. However, these proteins often contain structural binding regions that allow for the proper localization in the extracellular space which guides its correct function in a local and temporal manner. The regions that serve a structural function, although often associated with disease, tend to have a limited understanding. An example of this is the extracellular matrix protein Noggin; as part of the bone morphogenetic protein inhibitor family, Noggin serves a crucial regulatory function in mammalian developmental stages and later periods of life. Noggin's regular function, after its expression and extracellular release, is mediated by its retention in close proximity to the cellular surface by glycosaminoglycans, specifically heparin and heparan sulfate. Using a biophysical hybrid method approach, we present a close examination of the Noggin heparin binding interface, study its dynamic binding behaviors and observe supramolecular Noggin assemblies mediated by heparin ligands. This confirms previously suggested models of non‐covalent protein assemblies mediated through glycosaminoglycans that exist in the extracellular matrix. Further, structural analyses through molecular dynamics simulations allowed us to determine contribution energies for each protein residue involved in ligand binding and correlate this to disease associated mutation data. Our combination of various biophysical and computational methods that characterize the heparin binding interface on Noggin and its protein dynamics expands on the functional understanding of Noggin and can readily be applied to other protein systems.